Metabolic syndrome - from the mismatched evolutionary genome with the current obesogenic environment to the lifestyle modification as a primary care of free-living adults in a Brazilian community - Burini, Roberto C. [UNESP]; Kano, Hugo T. [UNESP]; Burini, Franz H.P. [UNESP]; Portero-McLellan, Katia C. (My University, 2017)
Metabolic syndrome (MetS) is a complex disorder associated with severe health complications reaching pandemic proportions worldwide. Converging data are now available to support the hypothesis that individuals with MetS underwent incorrect epigenetic programming during fetal/postnatal development due to inadequate maternal nutrition and metabolic disturbances. The mismatch of our ancient molded genome (thrifty phenotype) and a postnatal nutrition-rich environment might explain much of the epidemiology of current MetS. Hence, the development of MetS may be influenced by genetic as well as environmental factors related to unhealthy body composition, dietary inadequacy and a low level of physical fitness. This, so-called obesogenic-atherogenic environment has never existed in the past and, was consequently not part of selection pressure therefore, genetic adaptations might also not be expected. It seems that our genetically determined survival strategy turns against us now that we can eat whatever we want and whenever we want, and need little physical activity for food procurement. Thus, there is a general conclusion that MetS might caused by an interaction between genes and environment distracts from its causation by our current unfavorable environment. The identification of the underlying genes is nevertheless important from the point of view of health care. Meanwhile, we ought to keep looking back to our Paleolithic way of life translating its nutrition pattern and increasing our leisure physical activity into our obesogenic environment. In this chapter by adding the reviewed literature to our personal data from Botucatu Longitudinal Study (BLS) on Healthy Lifestyle Promotion as a primary care for non-communicable chronic diseases (Move for Health - Mexa-se Pró-saúde) we exploited our lifestyle management of MetS with nutrition and physical exercises and the major health effects. Our crosssectional studies described that MetS prevalence varied from 28% to 51%, higher in men, in those subjects over 60 yrs old, lower schoolarity, with low income and showing lower cardio-respiratory fitness along with normal daily physical activity levels and strength fitness. Additionally MetS was associated with inflammation and pro-oxidative status and the Framingham score for coronary artery disease. MetS was not related to a specific dietary pattern but significantly to a higher intake of saturated fat and low diet variety and lower fruit intake. Waist circumference was the mostly altered component of MetS followed by plasma triglycerides and glycemia, closely followed by blood pressure and HDL-cholesterol. Further on, our longitudinal studies involving lifestyle changing (LISC) protocols with dietary adequacy and physical exercises have shown a MetS reduction (7% to 29%) in a protocol duration-dependent effectiveness, from 10 to 24 weeks. Moreover, by associating nutrient specific strategies to dilute the overall energy consumption (e.g., dietary fiber) or W-3 fatty acids to reduce individual MetS components (e.g., triglycerides) the duration of protocol lasting could be abbreviated.